Cyanide Toxicity of Freshly Prepared Smoothies and Juices Frequently Consumed - Baker, A. (Eur J Nutr Food Saf, 2018)
AIMS: This study was conducted to detect the presence of cyanide in popular fruit and vegetable smoothies and juices marketed as raw and natural. STUDY DESIGN: Eleven (11) popular varieties of drinks were analyzed for total cyanide ((T)CN). Drinks contained raw vegetables and fruits, flax seeds, whole apples with seeds, raw almond milk, and pasteurized almond milk as ingredients. PLACE AND STUDY DURATION: Samples were collected from health food eateries located within Las Vegas, Nevada (USA) during the summer of 2017. METHODOLOGY: Fifty milliliters (mL) of a homogenized smoothie and juice drink and 1 gram of flax seeds were subjected to the above-referenced methods for sample preparation per USEPA Methods 9012B (digestion) followed by USEPA method 9014 (colorimetry). RESULTS: The highest (T)CN was detected in drinks containing raw flax seed followed by unpasteurized raw almond milk, then fresh whole apple juice. No (T)CN was observed in drinks that contained none of the above mentioned items (e.g. flax seed, raw almond milk) or those utilizing pasteurized ingredients. CONCLUSION: This study observed that (T)CN is present in smoothies and juices containing raw flax seeds, fresh whole apples, and/or unpasteurized almond milk. Concentrations were detected as high as 341 μg L(−1) in commercially available smoothies containing vegetables, raw flax seeds, almond milk and fruits. Smoothies with vegetables, fruits, unpasteurized almond milk, and no flax seeds contained 41 ug L(−1) (T)CN, while similar smoothies with pasteurized almond milk contained negligible to 9.6 ug L(−1) CN(-). Unpasteurized almond milk and raw flax seeds were the major sources of (T)CN in drinks. With the increased demand for raw and natural foods, there is a potential sublethal exposure of (T)CN by consumers.